2013
DOI: 10.5114/jcb.2013.34339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bladder distension on dosimetry of organs at risk in computer tomography based planning of high-dose-rate intracavitary brachytherapy for cervical cancer

Abstract: PurposeDistension and shape of urinary bladder may vary during intracavitary brachytherapy (ICBT) for cervical cancer, significantly affecting doses to bladder, rectum, sigmoid colon and small intestine and consequently late radiation toxicities. This study is to evaluate the effects of different fixed volume bladder distention on dosimetry, assessed by three dimensional image based planning, in different organs at risk during the treatment of cervical cancer with ICBT.Material and methodsForty seven cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
1
19
1
Order By: Relevance
“…In some other studies bladder distension was found to have no significant influence on bladder, rectum, and sigmoid doses 6 , 17 . This was contrary to what we observed in our study.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In some other studies bladder distension was found to have no significant influence on bladder, rectum, and sigmoid doses 6 , 17 . This was contrary to what we observed in our study.…”
Section: Discussionmentioning
confidence: 89%
“…The reason behind this might be methodological, as we compared the full bladder volume of a specific patient to her own empty bladder volume. In previous studies however, various bladder volumes of different patients were calculated and compared to one another; as such, additional patient specific features, such as OARs' wall elasticity or their relative distances, could potentially contribute to producing somewhat different results 6 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations